Influence of personality on digital library continuance / Norhidayu Md Yatim...[et al.] - Md Yatim, Norhidayu; Abdul Rahman, Abd Latif; Jamaludin, Adnan; Raja Omar, Raja Alwi; Alawi Idris, Ahmad Sufi; Mohd Paili, Shahruhaida Adayu (Universiti Teknologi MARA, Kedah, 2017)
Digital library brings many benefits to the users. Users can use the digital library at anytime and anywhere. Users'personality of digital library is important to be studied to understand the personality of users while using the digital library. They included agreeableness, extroversion, conscientiousness, openness to experience and neuroticism. To understand user's personality on digital library continuance, Technology Continuance Theory (TCT) was adopted to fulfill the purpose of the study. This study proposed a theoretical framework where it can help other organizations in determining the users' personality on their continuance use of services or information technology provided for them.